Gold alloy-based nanozyme sensor arrays for biothiol detection. Issue 11 (17th April 2020) - Lin, Junshu; Wang, Quan; Wang, Xiaoyu; Zhu, Yunyao; Zhou, Xi; Wei, Hui
Abstract : Schematic representation of biothol detection using gold alloy-based nanozyme sensor arrays. Abstract : Biothiols play an important role in living cells and are associated with many diseases. Thus, it is necessary to develop a facile, cost-effective, and convenient analytical method for the detection of biothiols. Nanozymes are functional nanomaterials with enzymatic activities. Due to their unique advantages ( e.g., low cost, high stability, and multifunctionality), nanozymes have been extensively used to construct sensing systems. Previous studies demonstrated colorimetric assays for biothiol detection because they could competitively inhibit the peroxidase-like activities of nanozymes. However, few studies were able to differentiate biothiols from each other. To address these challenges, herein, we first synthesized Au alloy nanozymes with better peroxidase-like activities than gold nanoparticles (AuNPs). Then, cross-reactive sensor arrays were constructed with three alloy nanozymes. Six typical biothiols ( i.e., glutathione, cysteine, dithiothreitol, mercaptoacetic acid, mercaptoethanol, and mercaptosuccinic acid) were successfully detected and discriminated by the as-prepared nanozyme sensor arrays. Moreover, the practical application of the nanozyme sensor arrays was demonstrated by discriminating biothiols in serum successfully.